Microneedle patches containing mesoporous polydopamine nanoparticles loaded with triamcinolone acetonide for the treatment of oral mucositis - Qu, Xiaoying; Guo, Xiaoli; Zhu, Tingting; Zhang, Zhe; Wang, Wanchun; Hao, Yuanping (Frontiers in Bioengineering and Biotechnology, 2023)
Oral mucositis (OM) is the most common disease of the oral mucosa, which affects people's daily production and life. Triamcinolone ointment is the common clinical drug for OM treatment. However, the hydrophobic properties of triamcinolone acetonide (TA) and the complex microenvironment of the oral cavity led to its low bioavailability and unstable therapeutic effects on ulcer wounds. Herein, dissolving microneedle patches (MNs) composed of mesoporous polydopamine nanoparticles (MPDA) loaded with TA (TA@MPDA), sodium hyaluronic acid (HA), and Bletilla striata polysaccharide (BSP) are prepared as the transmucosal delivery system. The prepared TA@MPDA-HA/BSP MNs exhibit well-arranged microarrays, high mechanical strength and fast solubility (< 3 minutes) properties. In addition, the hybrid structure improves the biocompatibility of TA@MPDA and expedites oral ulcer healing in the SD rat model through the synergistic anti-inflammatory and pro-healing effects of microneedle ingredients (hormones, MPDA and Chinese herbs extracts), with 90% less amount of TA compared with Ning Zhi Zhu®. TA@MPDA-HA/BSP MNs are shown to be their great potential as novel ulcer dressings for OM management.